بلاغة التصدير والتدبيج في شعر العباس بن الأحنف وديك الجن الحمصي - القاسم، ردينة; صبح، خلدون سعيد; الطالب، هايل محمد Altaleb, Hayel Mohammed (جامعة البعث, 2019)
This research seeks to study the arts of (expert and rehetoric) of abbas ibn al ahnaf and dick jinn al-homsi. To show their respective jokes in the use of rhythm and the decorative meaning and the beauty of their poetry, and to reveal the creative aspects that are unique to each. The research start by defining the export, the study of its muhiple sections according to the cohesive language relations between the words in the bilaterism according to the area of specific structure, then detail these relationships to show the basis of the correlation between the aesthetic values produced by export music and the significance it gives to the text. The research then discusies the concept of gradint with the study of the functions of colours single, bilateral and multiple; and reveal its rhetorical, aesthetic and psychological value and and its role in manifesting the intended meaning, then the research concludes with results that confirm. The role of this study in the semantic construction with in the manifertations of artistic and aesthetic expressions.
يسعى هذا البحث إلى دراسة فني (التصدير والتدبيج) عند العباس بن الأحنف وديك الجن الحمصي لإظهار طرائق كل منهما في توظيف الإيقاع والمعنى لتزيين وتجميل شعرهما؛ والكشف عن النواحي الإبداعية التي تفرد بها كل منهما. يبدأ البحث بتعريف التصدير، ودراسة أقسامه المتعددة تبعا للعلاقات اللغوية المتماسكة التي تقوم بين كلمتين في الثنائية الترديدية وفق مساحة مكانية محددة، ثم تفصيل هذه العلاقات لبيان أسس الترابط بين القيم الجمالية التي تفرزها موسيقى التصدير وبين الدلالة التي يضيفها على النص. ثم يتحدث البحث عن مفهوم التدبيج مع دراسة وظائف الألوان المفردة، والثنائية والمتعددة؛ وبيان قيمتها البلاغية والجمالية والنفسية، ودورها في تجلية المعنى المقصود. ثم يختم البحث بنتائج تؤكد دور هذه الدراسة في البناء الدلالي ضمن مظاهر التعبير الفني والجمالي.
Keywords: البلاغة العربية -- التصدير -- التدبيج -- العباس بن الأحنف -- ديك الجن الحمصي